Modern methods of conflict resolution in the arbitration process - T.R. Gizzyatov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The modern methods of resolving conflicts during the arbitration process were discussed. Mediation and judicial settlement as two types of conciliation were analyzed. The need for further promotion and development of this institution in the arbitration process was emphasized. The specifics of restoring the rights and legitimate interests by applying for judicial protection were considered. The paper outlines that consideration of the arbitration dispute on the merits, followed by ruling on the case, may put both the plaintiff and defendant, who are also counterparties, in such a position that the conflict as such remains, despite the decision made, which jeopardizes business relations and further cooperation. This situation may result in reduced turnover for narrow sectors, thereby putting them at risk. An alternative way, which is more likely to preserve relations between counterparties, is mediation, which is a real opportunity to maintain normal business relations between the parties, with the possibility of their subsequent development.